Expedient Access to Cyanated N‐Heterocycles by Direct Flow‐Electrochemical C(sp2)−H Activation. Issue 1 (5th November 2021) - Carvalho, Mary‐Ambre; Demin, Samuël; Martinez‐Lamenca, Carolina; Romanov‐Michailidis, Fedor; Lam, Kevin; Rombouts, Frederik; Lecomte, Morgan
Abstract: Nitriles are recurring motifs in bioactive molecules and versatile functional groups in synthetic chemistry. Despite recent progress, direct introduction of a nitrile moiety in heteroarenes remains challenging. Recent developments in electrochemical reactions pave the way to more practical cyanation protocols. However, currently available methods typically require hazardous cyanide sources, expensive mediators, and often suffer from narrow substrate scope and laborious reaction set‐up. To address the limitations of current synthetic methods, herein, an effective, sustainable, and scalable procedure for the direct C(sp 2 )−H cyanation of aromatic N‐heterocycles with a user‐friendly flow‐electrochemical set‐up is reported. Furthermore, high substrate and functional‐group tolerance is demonstrated, allowing late‐stage functionalization of drug‐like scaffolds, such as natural products and pharmaceuticals. Abstract : A robust and scalable C(sp 2 )−H electrocyanation of aromatic N‐heterocycles is reported. The protocol employs n Bu4 NCN as cyanide source and is performed in an undivided cell making it amenable to both batch and flow set‐ups. A total of 44 examples were synthesized in batch and 14 in flow, including privileged drug‐like heterocycles, such as pyrroles, imidazoles, (aza)indoles, and indazoles. The method displays high functional‐group tolerance and, for the first time, allows to directly cyanate unprotected N−H indoles.